Preventing Non-Communicable Diseases by Implementing the Free Health Screening Program - Wimar Anugrah Romadhon; Erni Setiyorini; Ning Arti Wulandari; Yeni Kartika Sari; Anita Rahmawati; Ulfa Husnul Fata; Raden Roro Dewi Rahmawaty Aktyani Putri; Thatit Nurmawati; Sandi Alfa Wiga Arsa; Sabrina Rahmatillah Azhar (STIKes Patria Husada Blitar, 2026)
Degenerative diseases are still a national problem and need special attention because if not handled properly, they will cause disability and even death. STIKes Patria Husada Blitar in collaboration with Visayas State University Philippines also succeeded in the government program, namely the Free Health Check (CKG). Together with the local health center, STIKes Patria Husada Blitar participated in health checks for the community including PTM screening, measuring body mass index, measuring blood pressure, checking blood sugar, cholesterol and uric acid levels, and other examinations. Participants in the Free Health Check were the community in the working area of ​​the Sananwetan Health Center as many as 57 participants. CKG activities were weighing, checking blood pressure, blood sugar levels, blood cholesterol levels, blood uric acid levels, eye screening, ear screening, dental screening, SADANIS examination and EKG examination. The CKG activity was held on Thursday, October 30, 2025 at the Residents' AssociationHall of Sananwetan Village. The examination results obtained that only 3.5% of the participants had a history of DM and 24.6% had a history of hypertension, as much as 42.1%; the majority of participants' blood pressure was pre-hypertension, namely 29.8%; the participants' blood sugar levels were mostly normal (<200 mg/dl), namely 59.6%; the participants' cholesterol levels were mostly normal (<200 mg/dl), namely 64.9%; and the participants' uric acid levels were mostly normal, namely 86%. The results of doctor consultations were only 24.6% who were advised to be referred to the Community Health Center or Health Facility. While the rest were advised to maintain their diet/regularly take medication. Universities can develop strategies for future community service activities by prioritizing promotive and preventive activities without neglecting curative and rehabilitative ones.